Antecedents of Accounting Culture and Consequences on Financial Reporting Quality: the Mediating Role of Quality Audit - Sari, Gema Ika; Lesfandra, Lesfandra (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study investigates the impact of accounting culture on financial reporting quality, with audit quality as a mediating factor. Using a quantitative, positivist approach, the research examined 60 internal auditors through a saturated sampling method. Results show that accounting culture positively influences financial reporting quality directly and through audit quality. Key findings highlight the importance of enhancing professionalism, motivation, adaptability, and transparency in accounting culture to improve financial reporting standards. Managerial implications emphasize fostering a strong accounting culture, maintaining transparency, and ensuring high audit quality to enhance stakeholder trust, prevent manipulation, and improve financial management. The study contributes to theories such as Accounting Culture Theory, which underscores the role of values and norms in promoting ethical practices; Positive Accounting Theory, which links audit quality to preventing errors and manipulation; and Stakeholder Theory, which stresses the importance of transparency in strengthening relationships and trust among stakeholders.